MASCULINITY PROTEST: REVEALING INFERIORITY IN MEN THROUGH NIZAR QABBANI’S ASYHADU ALLA IMRA’ATAN ILLA ANTI - Shinta Fitria Utami; Hindun Hindun; Taufik Amin Nur Wijaya (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2026)
Nizar Qabbani, a distinguished Arab poet from Syria, is widely recognized for his writing style, which, despite its linguistic simplicity, conveys profound meaning. Owing to this characteristic, his poetic works have garnered considerable scholarly attention within the field of Arabic literary studies. One of his notable poems, Asyhadu Alla Imra’atan Illa Anti, has frequently been examined for its thematic portrayal of love and womanhood. However, previous research has predominantly focused on the poem’s content, with limited attention given to the narrative voice—specifically, the first-person pronoun “I”—through which the poem’s message is articulated. This narrative persona, interpreted as a representation of the male subject, is portrayed as occupying a position of inferiority. This study aims to investigate the depiction of male inferiority within the poem. Employing a qualitative method, the research analyzes the text by collecting words, phrases, and sentences through note-taking techniques. The data are subsequently examined using a semiotic approach and content analysis, informed by Adlerian psychoanalytic theory. The findings suggest that the manifestation of male inferiority in the poem is closely linked to societal expectations imposed on men, particularly within the framework of patriarchal cultural structures.